PEMBERDAYAAN DAN PELATIHAN REMAJA MESJID AL-ALI SEBAGAI AGEN MODERASI BERAGAMA - Ahsani Amalia Anwar; Nurlaila Tuanany; Belly Isayoga Kristyowidi; Muis S.A. Pikahulan; Ajuan Tuhuteru; Ferry Rangi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
Understanding of religious teachings is something that must be done by every adherent. This understanding is not only about the teaching itself but also understanding the various interpretations of the teaching. When a person can understand the various interpretations that exist, he will be more likely to take the middle path (moderate) from what he understands. An extreme attitude in understanding religious values ​​will emerge when a believer of a religion has no alternatives. This activity was carried out by identifying the problems faced by youth of the Al Ali mosque in internalizing the notion of religious moderation, so PkM activities were held with the theme